Plasma total cell-free DNA (cfDNA) is a surrogate biomarker for tumour burden and a prognostic biomarker for survival in metastatic melanoma patients. (January 2018) - Valpione, S.; Gremel, G.; Mundra, P.; Middlehurst, P.; Galvani, E.; Girotti, M.R.; Lee, R.J.; Garner, G.; Dhomen, N.; Lorigan, P.C.; Marais, R.
Abstract: Introduction: Tumour burden is a prognostic biomarker in metastatic melanoma. However, tumour burden is difficult to measure and there are currently no reliable surrogate biomarkers to easily and reliably determine it. The aim of this study was to assess the potential of plasma total cell free DNA as biomarker of tumour burden and prognosis in metastatic melanoma patients. Materials and methods: A prospective biomarker cohort study for total plasma circulating cell-free DNA (cfDNA) concentration was performed in 43 metastatic melanoma patients. For 38 patients, paired blood collections and scan assessments were available before treatment and at first response evaluation. Tumour burden was calculated as the sum of volumes from three-dimensional radiological measurements of all metastatic lesions in individual patients. Results: Baseline cfDNA concentration correlated with pre-treatment tumour burden (ρ = 0.52, P  < 0.001). Baseline cfDNA levels correlated significantly with hazard of death and overall survival, and a cut off value of 89 pg/μl identified two distinct prognostic groups (HR = 2.22 for high cfDNA, P  = 0.004). Patients with cfDNA ≥89 pg/μl had shorter OS (10.0 versus 22.7 months, P  = 0.009; HR = 2.22 for high cfDNA, P  = 0.004) and the significance was maintained when compared with lactic dehydrogenase (LDH) in a multivariate analysis. We also found a correlation between the changes of cfDNA and treatment-related changes in tumour burden (ρ = 0.49, P  = 0.002). In addition, the ratio between baseline cfDNA and tumour burden was prognostic (HR = 2.7 for cfDNA/tumour volume ≥8 pg/(μl*cm 3 ), P  = 0.024). Conclusions: We have demonstrated that cfDNA is a surrogate marker of tumour burden in metastatic melanoma patients, and that it is prognostic for overall survival. Highlights: A prospective biomarker cohort study for total circulating cell-free DNA (cfDNA) in plasma was performed in metastatic melanoma patients. Paired blood collections and scan assessments were studied. CfDNA was measured by means of droplet digital Polymerase Chain Reaction and tumour burden was calculated as the sum of volumes from three-dimensional radiological measurements of all metastatic lesions in individual patients. Baseline plasma cfDNA level correlates to tumour volume. Plasma cfDNA level and is a surrogate biomarker for tumour burden and tumour burden changes after treatment. Plasma cfDNA level is a prognostic marker for survival in metastatic melanoma patients.